98/5000 Interests, motivations and perceptions of Peruvian fishing entrepreneurs towards sustainable fishing - Paredes Tarazona, Mildred (2002)
The fact ors psycosocials are studied: Perception and interests toward the sustainable fishing in a representative sample of Managers Exporters Fishing Peruvians. The analysis descriptive-correlational of the data with statistical not parametric the point out that the variables are not very significant for a behavior in the perspective of the sustainable development.